Abusive Supervision and Employee Well‐Being: The Moderating Effect of Power Distance Orientation. Issue 2 (4th March 2013) - Lin, Weipeng; Wang, Lei; Chen, Shuting
Abstract : Researchers generally believe that abusive supervision leads to poor employee well‐being (e.g. poor mental health and lower job satisfaction). However, these relationships are not always observed. Based on the cognitive appraisal theory, the current research extended the content domain of abusive supervision research by examining the moderating effect of power distance orientation (the extent to which an individual accepts the unequal distribution of power in institutions and organisations), a kind of cultural value, on these relationships. We tested two independent samples ( N1 = 762 and N2 = 347) using different methods. Results showed that employees' power distance orientation moderated the relationships of abusive supervision with employee psychological health and job satisfaction, such that the negative relationships were weaker for employees with higher power distance orientation. The findings suggest the adaptive function of cultural values employees hold in organisational behavior. The implications for theory and practice are discussed.